Integers

1. (-26)-39 =

2. 3-(-9) =

3. 3+(-8)=

4. (-4)-(-8)=

5. (-16)-(23) =

Integers

1. (-26)-39 =

2. 3-(-9) =

3. 3+(-8)=

4. (-4)-(-8)=

5. (-16)-(23) =

6. (-6)-(-9)=

7. 13-(-59)=

8. (-11)-(-98)=

9. 3+(-4)=

10. (-1)+3=​

2 thoughts on “Integers<br /><br />1. (-26)-39 =<br /><br />2. 3-(-9) =<br /><br />3. 3+(-8)=<br /><br />4. (-4)-(-8)=<br /><br />5. (-16)-(23) =”

  1. Step-by-step explanation:

    1. (-26)-39 =-65

    2. 3-(-9) =13

    3. 3+(-8)=-5

    4. (-4)-(-8)= 4

    5. (-16)-(23) =-39

    6. (-6)-(-9)=3

    7. 13-(-59)=72

    8. (-11)-(-98)=87

    9. 3+(-4)=-1

    10. (-1)+3=2

Leave a Comment